2016
DOI: 10.7305/automatika.2016.10.1427
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Accumulation Clustering with Possibilitic Fuzzy C-Means base clustering approach to disease diagnosis

Abstract: Original scientific paperTraditionally, supervised machine learning methods are the first choice for tasks involving classification of data. This study provides a non-conventional hybrid alternative technique (pEAC) that blends the Possibilistic Fuzzy CMeans (PFCM) as base cluster generating algorithm into the 'standard' Evidence Accumulation Clustering (EAC) clustering method. The PFCM coalesces the separate properties of the Possibilistic C-Means (PCM) and Fuzzy C-Means (FCM) algorithms into a sophisticated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…For publications in 2000-2009, data sources used were surveys or questionnaire data [30], patient or medical data [31][32][33], clinical or health care research datasets [34], and patient or disease registries [35]. For publications in 2010-2019, more data sources were used, including surveys or questionnaire data [12,24,26,, interviews or focus groups [25,27,28,37,69,94,, patient or medical data [23,, clinical or health care research datasets [23,[143][144][145][146][147][148][149][150][151][152][153], patient or disease registries [29,67,154,155], and social media (Facebook [156,157], Twitter [158,159], Quora [22], and WhatsApp [160]) and new social media datasets [161].…”
Section: Publication-based Analysismentioning
confidence: 99%
“…For publications in 2000-2009, data sources used were surveys or questionnaire data [30], patient or medical data [31][32][33], clinical or health care research datasets [34], and patient or disease registries [35]. For publications in 2010-2019, more data sources were used, including surveys or questionnaire data [12,24,26,, interviews or focus groups [25,27,28,37,69,94,, patient or medical data [23,, clinical or health care research datasets [23,[143][144][145][146][147][148][149][150][151][152][153], patient or disease registries [29,67,154,155], and social media (Facebook [156,157], Twitter [158,159], Quora [22], and WhatsApp [160]) and new social media datasets [161].…”
Section: Publication-based Analysismentioning
confidence: 99%
“…These efforts would improve the effectiveness of image-based approaches used in cervical cancer diagnosis and treatment. Later, we hope to exploit these strategies (and others in [ 35 ]) in image-based detection of other carcinogens.…”
Section: Discussionmentioning
confidence: 99%
“…Abdullah M. et al, concluded that the standard techniques in the methods of calculating accuracy and execution time for both the artificial and actual clinical databases [13].…”
Section: Literature Surveymentioning
confidence: 99%